Conceptualizing Network Configurations as Dynamic Capabilities for Emerging Market Born Globals. Issue 2 (22nd February 2018) - Ngasri, Nurul Efifi Mohamad; Freeman, Susan
Abstract: The literature on international entrepreneurship (IE) provides insufficient understanding on network-based capabilities that born globals (BGs) undertake to maintain post-entry competitive advantages. Most organizational studies to date seem to address only network positioning, therefore providing inadequate understanding on network dynamics. More importantly, configuration of network dynamics from the perspective of the focal firm has been underexplored. This study seeks to fill this gap by asking the following question: How do emerging market (EM) BGs undertake network configuration during internationalization? We suggest network configuration as a primary construct to provide better understanding of network management based on the dynamic capabilities view (DCV). Particularly, in the face of increasing emerging market turbulence, network configuration provides an understanding of a BG's growth despite a high degree of environmental dynamism. Propositions are developed and future research directions are offered.